THE IMPACT OF HOUSING DEVELOPMENT ON THE SOCIO-ECONOMY OF INDIGENOUS PEOPLE IN ALALAK SUB-DISTRICT, BATOLA DISTRICT - Triyono, Sigit; Arisanty, Deasy; Angriani, Parida; Syarifuddin, Syarifuddin; Rahmia, Sovia Husni (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2024)
Housing development on the outskirts of the city often causes significant changes in land use. Land that was previously used for agricultural purposes, plantations, or even as green open space, is converted into residential areas. The impact of this change is felt by the surrounding community who previously depended on these natural resources. This article describes how the impact of housing development in the alalak sub-district area of Batola district. This research uses a quantitative approach and data analysis. Through the measurement of number-based variables, researchers can minimize subjective bias. This allows hypothesis testing with more accurate and reliable results. The results of this research are described explicitly including: 1) the impact of housing development in Alalak Sub-district, Barito Kuala Regency, on land use change and disaster risk, particularly flood risk in the area: 2) housing development in Alalak Sub-district affects the social aspects and economic welfare of the local community, especially the indigenous population: 3) policy recommendations that can be proposed to reduce the negative impacts of housing development on local communities, and how these policies can support more inclusive regional development.